2022
DOI: 10.3390/antiox11112286
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Type- and Dose-Specific Transcriptional Responses across Healthy and Diseased Mammalian Tissues

Abstract: Ionizing radiation (IR) is a genuine genotoxic agent and a major modality in cancer treatment. IR disrupts DNA sequences and exerts mutagenic and/or cytotoxic properties that not only alter critical cellular functions but also impact tissues proximal and distal to the irradiated site. Unveiling the molecular events governing the diverse effects of IR at the cellular and organismal levels is relevant for both radiotherapy and radiation protection. Herein, we address changes in the expression of mammalian genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 124 publications
1
11
0
Order By: Relevance
“…Low doses of ionizing radiation may induce specific effects that are not seen after higher doses, one of these being the HRS effect for doses below approximately 0.5 Gy. In a recent meta-analysis of 39 studies investigating gene expression after exposure to ionizing radiation, Sagkrioti et al found that while doses in the 0.6-2.0 Gy range generally induced genes related to ROS metabolism, doses below 0.5 Gy were associated with the expression of genes related to cytokine and inflammatory response pathways [141].…”
Section: Tgf-β3 and Low Dose-rate Irradiation-sustained Induction Or ...mentioning
confidence: 99%
“…Low doses of ionizing radiation may induce specific effects that are not seen after higher doses, one of these being the HRS effect for doses below approximately 0.5 Gy. In a recent meta-analysis of 39 studies investigating gene expression after exposure to ionizing radiation, Sagkrioti et al found that while doses in the 0.6-2.0 Gy range generally induced genes related to ROS metabolism, doses below 0.5 Gy were associated with the expression of genes related to cytokine and inflammatory response pathways [141].…”
Section: Tgf-β3 and Low Dose-rate Irradiation-sustained Induction Or ...mentioning
confidence: 99%
“…Comparing these results to existing literature, the downregulation of DNA damage repair genes by 48 hours provide further evidence that low-moderate dose proton irradiation can inhibit DNA damage repair [ 95 ]. A recent study found identified radiation type- and dose-specific transcriptional responses across healthy and diseased mammalian tissues reported that low doses up to 0.5 Gy are related with cytokine cascades, while higher doses with ROS metabolism [ 96 ]. This study reported significantly enriched GO pathways associated with 0.6–2 Gy doses of IR that were also significantly enriched in our study: negative regulation of mitotic cell cycle (GO:0045930), negative regulation of cell cycle process (GO:0010948), mitotic cell cycle phase transition (GO:0044772), organelle fission (GO:0048385) [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found identified radiation type- and dose-specific transcriptional responses across healthy and diseased mammalian tissues reported that low doses up to 0.5 Gy are related with cytokine cascades, while higher doses with ROS metabolism [ 96 ]. This study reported significantly enriched GO pathways associated with 0.6–2 Gy doses of IR that were also significantly enriched in our study: negative regulation of mitotic cell cycle (GO:0045930), negative regulation of cell cycle process (GO:0010948), mitotic cell cycle phase transition (GO:0044772), organelle fission (GO:0048385) [ 96 ]. In addition, their study reported that transcriptional responses such as immunomodulation, inflammation, oxidative stress responses, and cell death were different from those caused by lower doses or less energetic radiation [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has mutagenic and/or cytotoxic effects that affect tissues both near and far from the irradiated area. These effects affect vital biological processes 5,6 . In numerous tissues and organs of rodents, N ‐nitrosodiethylamine (NDEA) is a strong carcinogen and promoter of lipid peroxidation (LPO) and/or pro‐oxidant changes 7 .…”
Section: Introductionmentioning
confidence: 99%
“…These effects affect vital biological processes. 5,6 In numerous tissues and organs of rodents, N-nitrosodiethylamine (NDEA) is a strong carcinogen and promoter of lipid peroxidation (LPO) and/or pro-oxidant changes. 7 The interaction between NDEA and other LPO generators, such as gamma radiation, is of relevance since LPO may be induced in rats administered NDEA, 8 In a short-term radiation carcinogenesis model, the NDEA can raise the danger of gamma ray-induced damage.…”
Section: Introductionmentioning
confidence: 99%